Correction: Taking advantage of the disadvantage: employing the high aqueous instability of amorphous calcium carbonate to realize burst drug release within cancer cells. Issue 33 (29th July 2020) - Wang, Cheng; Chen, Shaoqing; Yu, Qin; Hu, Fuqiang; Yuan, Hong
Abstract : Correction for 'Taking advantage of the disadvantage: employing the high aqueous instability of amorphous calcium carbonate to realize burst drug release within cancer cells' by Cheng Wang et al., J. Mater. Chem. B, 2017, 5, 2068–2073, DOI: ; 10.1039/C6TB02826H .